Knowledge and perceptions of kangaroo mother care among health providers: a qualitative study - Hadi Pratomo; Tiara Amelia; Fatmawati Nurlin; Asri C. Adisasmita (The Korean Pediatric Society, 2020)
Background Indonesia is one of the countries with the highest preterm birth rate. Preterm infants are more likely than term and normal weight infants to experience neonatal mortality and morbidity due to acute respiratory, gastrointestinal, immunologic, central nervous system, hearing, and vision problems. Kangaroo mother care (KMC) is a proven cost-effective intervention to help reduce mortality rates among preterm infants; however, it has not been fully implemented in hospitals. Purpose Assess KMC knowledge and perceptions among health providers. Methods This qualitative study was conducted from December 2015 to April 2016 and consisted of 21 in-depth interviews and 3 focus group discussions (FGDs). The 3 categories of health personnel in the study were clinical providers, hospital management representatives, and Indonesian Midwife Association members. Results Most health providers know about the benefits of KMC including stabilizing temperatures, weight gain, and maternal-infant bonding and reducing human resources and labor costs. They were also aware of which newborns were eligible for KMC treatment. Their knowledge was mostly gained from observation or obtained from pediatricians and personal experience. They believed that a low birth weight infant in an incubator could not be treated with KMC and that it could only be practiced if a special gown was used when holding the baby. This perception could be caused by a lack of formal KMC training, leading to misunderstanding of its aspects. Conclusion In conclusion, KMC knowledge of clinical providers in the 2 hospitals was sufficient, primarily due to their health-related educational background. Some perceptions could be potential barriers to or facilitate the implementation of KMC practice. These perceptions should be considered in future KMC training designs.